An innovative approximation concerning the diffusion and electrical conductivity tensor at critical altitudes within the F-region of ionospheric plasma at low latitudes - Yasar, Mehmet; Kurt, Kadri; Yesil, Ali (De Gruyter Poland Sp Z O O, 2025)
This study examines a new method for comprehending diffusion and electrical conductivity tensors in the F-region of ionospheric plasma at low latitudes. The research formulates equations for the real diffusion coefficients by combining electrical conductivity and diffusion processes into a single analytical equation. The coefficients of diffusion and electrical conductivity possess both real and imaginary components as a result of the Earth's real magnetic field configuration. At low latitudes, the constituents of the diffusion tensor display elevated values at night compared to those during the daytime. It has been observed that magnetic diffusion coefficient ratios are minimum in conditions such as equinox days and periods of increased solar activity. This illustrates the impact of solar activity on fluctuations in electron density and ionospheric conductivity. This research examines the equator and demonstrates variability with respect to latitude and temporal factors. The results highlight the influence of the equatorial anomaly on ionospheric diffusion, specifically on the transport of ionized particles caused by the E x B drift, which results in areas of fluctuating electron density. The ultimate goal of this work is to provide numerical evaluations that address a gap in ionospheric transport processes research by integrating diffusion and conductivity into a functional correlation, thus establishing a foundation for future studies.
Keywords: ionosphere; complex diffusion coefficients; electrical conductivity